Pengungsi Rohingnya dan Tindakan People Smuggling dalam Hukum Internasional - Kaliky, Sultan Kanon; Wattimena, Josina Augustina Yvonne; Noya, Ekberth Vallen (Faculty of Law Universitas Pattimura, 2024)
Humanitarian disputes throughout the world continue, causing discomfort for those who suffer from these problems, so they try to seek refuge in several countries that are considered safe to avoid conflicts in other countries. When they calm down, people will come together to save themselves from human cruelty towards each other. The aim of the writing carried out by the author is to analyze and discuss the arrival of Rohingya refugees in Indonesia and the act of human smuggling. The research method used by the author is normative juridical where research is carried out to obtain data through literature studies, namely various literature and scientific materials, brochures and so on. The research results show that the regulation of human trafficking crimes, both at the international and national levels, can influence (or cloud) the international protection that should be provided to asylum seekers. However, on the other hand, human smuggling can weaken asylum seekers and potentially violate the principle of non-refoulement.